2009
DOI: 10.1143/apex.2.032102
|View full text |Cite
|
Sign up to set email alerts
|

High Power and High Resolution Near-Infrared Light Source for Optical Coherence Tomography Using Glass Phosphor and Light Emitting Diode

Abstract: We have fabricated a novel near-infrared light source for optical coherence tomography (OCT) using a glass phosphor and a light emitting diode (LED) as the excitation source. We used 1.glass as the phosphor to obtain wideband light emission around 1000 nm. We observed a full-width at half-maximum (FWHM) as wide as 98 nm with an output power as high as 1 mW. The interference signal showed a coherence length of 4.6 m. This value indicates that the depth resolution of the OCT is twice as high as that of conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 7 publications
0
23
1
Order By: Relevance
“…For example, Ln-doped glasses are known as phosphor materials. [34] The local structure and electronic structure of the dopant is known to be essential for the optical property of this kind of phosphor. EXAFS spectroscopy is a possible local structure analysis technique; however, it is generally difficult to estimate local structure because of its amorphous nature.…”
Section: Sm-doped Glassesmentioning
confidence: 99%
“…For example, Ln-doped glasses are known as phosphor materials. [34] The local structure and electronic structure of the dopant is known to be essential for the optical property of this kind of phosphor. EXAFS spectroscopy is a possible local structure analysis technique; however, it is generally difficult to estimate local structure because of its amorphous nature.…”
Section: Sm-doped Glassesmentioning
confidence: 99%
“…Since OCT is based on the Michelson interferometer, a low-coherence broadband light source has some advantages for ultrahigh axial resolution [1]. To avoid multiple scattering in skin tissue and fiber loss, the operating wavelength is necessary to be in the range of 1.0 μm-1.3 μm [2].…”
Section: Introduction Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…For the applications of LED on OCT, Fuchi et al have demonstrated several near-infrared (NIR) sources, including size-dispersed quantum dots LED, 12) and NIR glass phosphors pumped by 590 nm visible LED. 13,14) Broadband emissions with 4.6 m interference signals were observed with high power using NIR glass phosphors and an LED as excitation source. 14) Thus, finding the framework for linking broadband glass-phosphor-based light source and performing corresponding ultrahigh-resolution optical coherence imaging is an important topic in the following research.…”
mentioning
confidence: 99%
“…13,14) Broadband emissions with 4.6 m interference signals were observed with high power using NIR glass phosphors and an LED as excitation source. 14) Thus, finding the framework for linking broadband glass-phosphor-based light source and performing corresponding ultrahigh-resolution optical coherence imaging is an important topic in the following research.…”
mentioning
confidence: 99%